SISTEM STRESSLEVEL UNTUK MENGUKUR TINGKAT STRES PADA DATA MAHASISWA DI MASA PANDEMI - Ester Manda Caroline (2022)
The Indonesian government decided to implement a social distancing system and a Large-Scale Social Restrictions (PSBB) policy to stop the dangerous growth in the spread of COVID-19 in Indonesia. Increased stress among students, especially university students, is a new issue caused by the implementation of a distance learning system during the pandemic from home. Students' attitudes and behavior changed as a result of increased stress, especially in their emotional feelings. A method is needed to monitor stress levels to better know a person's stress level and how to deal with it. The DASS 42 stress parameter measuring instrument was used as a website-based stress level measurement method in this study. Users, namely students, can use the combination of the system with the DASS 42 parameter stress measuring instrument easily and can get information about stress and the right solution by utilizing information technology. Based on the research results, the designed website-based StressLevel system can help students measure the level of stress they experience during a pandemic. In addition, this system can also display information in the form of solutions to overcome the current stress level.